Effect of Coronary Collaterals on Prognosis in Patients Undergoing Primary Percutaneous Coronary Intervention for Acute ST-Segment Elevation Myocardial Infarction: A Meta-Analysis. (October 2018) - Cui, Kongyong; Lyu, Shuzheng; Song, Xiantao; Yuan, Fei; Xu, Feng; Zhang, Min; Zhang, Mingduo; Wang, Wei; Zhang, Dongfeng; Tian, Jinfan
The impact of coronary collaterals on the prognosis in patients with acute ST-segment elevation myocardial infarction (STEMI) in the era of coronary revascularization remains controversial. The purpose of this meta-analysis was to investigate the effect of coronary collateral on clinical outcomes, especially mortality (≥6 months), in patients undergoing primary percutaneous coronary intervention (PCI) for STEMI. Eligible observational studies were selected by searching PubMed, EMBASE, and Cochrane Library up to August 9, 2017. Overall, 14 observational studies involving 10 411 patients were included. Coronary collaterals were found to reduce the risk of long-term mortality (≥6 months; risk ratio [RR]: 0.65, 95% confidence interval [CI]: 0.55-0.76) as well as in-hospital plus 30-day mortality (RR: 0.61, 95% CI: 0.47-0.78) in patients undergoing PCI for STEMI. In addition, pooling the risk-adjusted or propensity-matched data showed a significant reduction in long-term mortality (RR: 0.68, 95% CI: 0.49-0.95) and in-hospital plus 30-day mortality (RR: 0.27, 95% CI: 0.13-0.55) in patients with collateral circulation. However, no significant difference was found in the risk of recurrent myocardial infarction and target vessel revascularization between the 2 groups. Therefore, it was found that coronary collaterals have a beneficial effect on long-term survival (≥6 months) as well as in-hospital plus 30-day survival in patients undergoing primary PCI for STEMI.